DEVELOPING AN E-BOOK USING CANVA ON THE MATERIAL ABOUT OUR EARTH TO IMPROVE CRITICAL THINKING SKILLS IN DIFFERENTIATED LEARNING - Suningsih, Siti; Novita, Lina; Sukmanasa, Elly (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study is to develop an e-book using Canva for the material "Getting to Know Our Earth" to improve critical thinking skills in differentiated learning. This objective highlights four things, namely the characteristics of Canva-based e-books, improving students' critical thinking, the feasibility of e-books, and students' responses to e-books. The method used in this study is research and development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of the study show that the developed e-book has attractive, interactive, and contextual visual characteristics. This media has proven to be suitable for use, effective in encouraging increased critical thinking skills and student participation, and has received positive responses from students and teachers. This e-book is also considered relevant to the needs of 21st-century learning.